2022
DOI: 10.21203/rs.3.rs-1537070/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triglyceride glucose index for the detection of the severity of coronary artery disease in different glucose metabolic states in patients with coronary heart disease: a RCSCD-TCM study in China

Abstract: Background: The triglyceride glucose (TyG) index is a new marker associated with atherosclerosis. This study aimed to assess the association between the TyG index and the severity of coronary artery disease (CAD) in patients with coronary heart disease (CHD) and further explore the association between the TyG index and CAD severity in different glucose metabolic states.Methods: This multi-centre retrospective study included 731 CHD patients between September 1, 2014 to September 30, 2020 in China. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…Coronary angiography (CAG) as the gold standard for diagnosing CAD is an accurate and widely used imaging modality that aims to identify the number and degree of coronary artery stenosis. Participants with ≥ 50% lumen stenosis in at least one major coronary artery based on CAG findings were diagnosed with CAD [19]. Furthermore, the severity of CAD was based on the number of stenotic vessels and has a crucial role in the prognosis of CVD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronary angiography (CAG) as the gold standard for diagnosing CAD is an accurate and widely used imaging modality that aims to identify the number and degree of coronary artery stenosis. Participants with ≥ 50% lumen stenosis in at least one major coronary artery based on CAG findings were diagnosed with CAD [19]. Furthermore, the severity of CAD was based on the number of stenotic vessels and has a crucial role in the prognosis of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the severity of CAD was based on the number of stenotic vessels and has a crucial role in the prognosis of CVD. Participants with multi-vessel CAD are at higher risk for CVD than those with single-vessel CAD, especially those with an abnormal glucose metabolic status [19,20]. A recent study suggested that the TyG index is associated with the risk of multi-vessel CAD for the DM population, but not with that for individuals with prediabetes mellitus (pre-DM) or normoglycemia (NGR) [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that the TyG index can be used as a substitute index for IR, which is a simpler and faster assessment of the body's IR status (13,(25)(26)(27). Several studies have found that the TyG index is significantly associated with the occurrence of atherosclerotic cardiovascular disease (28)(29)(30)(31). A cohort study found that, in long-term follow-up, the TyG index can identify people at high risk for cardiovascular events (28).…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, a meta-analysis summarizing multiple cohort studies found that after adjusting for the effects of age, gender, and DM, the TyG index was still independently associated with the risk of cardiovascular disease (29). In a RCSCD-TCM study, Su et al conducted a retrospective analysis of 731 patients with CAD and found that the TyG index was associated with the severity of CAD, and an elevated TyG index could increase the risk of coronary multivessel disease (30). Alessandra et al analyzed baseline data from patients in secondary cardiac care and found that the TyG index was associated with metabolic risk factors for the heart, and that a high level of the TyG index was more likely to develop symptomatic CAD (31).…”
Section: Discussionmentioning
confidence: 99%